IMPLEMENTASI HUKUM ACARA PIDANA DALAM PROSES PENYIDIKAN OLEH KEPOLISIAN - Nugraha, Aliffiansyah Sam Adhitya; Hartoyo, Hartoyo; Damayanti, Sri Sukmana (Bureaucracy Journal : Indonesia Journal of Law and Social-Political Governance, 2025)
This study aims to examine the implementation of criminal procedural law in the investigation process by the Mojokerto Police Department. The research method used is a normative juridical approach with field studies to obtain factual data. The results indicate that the implementation of investigations at the Mojokerto Police Department generally complies with the provisions of the Criminal Procedure Code (KUHAP), including the stages of summons, arrest, detention, examination, and transfer of case files. Investigators also strive to comply with the principles of legal protection, including fulfilling the suspect’s right to legal counsel and protection from arbitrary detention, although technical and non-technical obstacles remain. These obstacles include limited human resources, suboptimal supporting facilities, and low public understanding of the law. Efforts to overcome these obstacles are carried out through training for investigators, improving cross-agency coordination, and legal outreach to the community